2022
DOI: 10.48550/arxiv.2204.04008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taxonomy of Attacks on Open-Source Software Supply Chains

Abstract: The widespread dependency on open-source software makes it a fruitful target for malicious actors, as demonstrated by recurring attacks. The complexity of today's opensource supply chains results in a significant attack surface, giving attackers numerous opportunities to reach the goal of injecting malicious code into open-source artifacts that is then downloaded and executed by victims.This work proposes a general taxonomy for attacks on opensource supply chains, independent of specific programming languages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Attackers also compromise the repositories themselves and not just individual packages [22], [31]. Recent work has created a comprehensive taxonomy of attacks on the OSS supply chain [32].…”
Section: A Software Supply Chain Attacksmentioning
confidence: 99%
See 1 more Smart Citation
“…Attackers also compromise the repositories themselves and not just individual packages [22], [31]. Recent work has created a comprehensive taxonomy of attacks on the OSS supply chain [32].…”
Section: A Software Supply Chain Attacksmentioning
confidence: 99%
“…An alert associated with a malicious package is considered a true positive, while an alert on a benign package is a false positive. a) Tool selection: We used the work of Ladisa et al [32] and surveyed existing literature to create a list of candidate Python malware detection tools. Notably, we did not include vulnerability scanning tools such as Security.py, Hawkeye, and Salus because these packages (by design) tend to have many findings on benign code, and this work studies only deliberately malicious software.…”
Section: A Approachmentioning
confidence: 99%
“…Further, prior research has shown that code review helps ensure higher code quality [29] and can prevent the introduction of new security vulnerabilities [17]. Ladisa et al [26] have developed an attack taxonomy for open source supply chain attacks, where they have mentioned code review as a safeguard against the attack vector inject into sources of legitimate package.…”
Section: Introductionmentioning
confidence: 99%